Desinformação e circulação textual: cartografia comunicável da extrema-direita brasileira na pandemia COVID-19 - Santos, Isabela Marília Santana (2025)
In this study, from a textual-discursive perspective, we present an investigation into the process of disinformation – in order to reflect on language and use, politics and technology, and text and its socio-discursive practices – that legitimizes it as a political mechanism for the discursive construction of federal management in the Covid-19 pandemic. To this end, we mapped several textual models in order to build a communicable cartography (BRIGGS, 2005) and present a sample that represents what disinformational political communication was in the years that followed this historic health event in Brazil, considering online Bolsonarism as a manifestation of digital populism of the Brazilian far-right (CESARINO, 2020). With post-digital societies (BLOMMAERT, 2020), human interaction, social and linguistic practices, and even institutions, such as the political institution, have undergone changes and become part of a new linguistic and technological order. Politics began to function and communicate within a more sophisticated architecture, with clearly signaled, faster, and more immediate effects of meaning. Thus, by narrating the pandemic episodes and the trajectories assumed by the texts when reconstructing the pandemic Bolsonaro communicability, interpreting their entextualizations, grafts (BAUMAN AND BRIGGS, 1990), and reconstructed meanings, our objective is to analyze Bolsonaro metapragmatic models present in the interpretations and productions of these textual-discursive and interactive events, bringing to the focus of the discussion the textual circulation, the textual trajectories, the role of the processes of recategorization of discourse objects as legitimizers of the textual-interactive constructions, together with the entextualizations and indexicality, of the studied theme – disinformation. As our starting point is the interest in the text and its developments, we will also reflect and aim to contribute to the discussion that in language, it is possible to consider the issue of language based on the constitutive instability of (MONDADA AND DUBOIS, 2003) linguistic categories for the construction of the process of textual referencing, a phenomenon in constant discursive (re)elaboration (CAVALCANTE ET AL, 2010), which will be complemented and expanded in this thesis by studies of indexicality (SILVERSTEIN, 1976; SILVA, 2014), which transports the meanings to an ideological, political and discursive power level, as required by the political corpus in question. The theoretical-methodological approach for the (re)construction of this communicable cartography is to follow the trajectories of texts on preventive measures during the pandemic (masks, vaccines, and attempts at “early treatment”) through the textual tracking method (FABRÍCIO, 2014; BOAVENTURA, 2018), which consists of following digital textual models to generate data, focusing on multifaceted, linguistic, political, social, and historical dimensions “that constitute deterritorialized and multisituated forms of understanding/constructing social experiences” (BOAVENTURA, 2018, p. 19). This research aims to contribute to studies in Textual Linguistics by recognizing the text as a process and not as a product, in addition to moving in a less traditional and more transformative direction regarding theories of communication, language, and text in order to be able to account for the object analyzed: politically engaged, textually mapped, and metapragmatically oriented disinformation.